Crystallization to polycrystalline silicon thin film and simultaneous inactivation of electrical defects by underwater laser annealing - Machida, Emi (American Institute of Physics, 2012)
We propose a low-temperature laser annealing method of a underwater laser annealing (WLA) for polycrystalline silicon (poly-Si) films. We performed crystallization to poly-Si films by laser irradiation in flowing deionized-water where KrF excimer laser was used for annealing. We demonstrated that the maximum value of maximum grain size of WLA samples was 1.5 μm, and that of the average grain size was 2.8 times larger than that of conventional laser annealing in air (LA) samples. Moreover, WLA forms poly-Si films which show lower conductivity and larger carrier life time attributed to fewer electrical defects as compared to LA poly-Si films.